(untitled) (Mustansiria Dental Journal, 2024)
The aim of this survey is to investigate the prevalence of malocclusion and different morphological features of dental occlusion in an Iraqi sample. The sample consisted of (218) dental student at college of Dentistry, Baghdad university, aged (18-21 year) & of both sexes. Were clinically evaluated after exclusion of students who have received any type of orthodontic treatment. The students also divided into two groups, the group who have received extraction of any tooth and the other group who have no extraction. Ag ,Of the sample (26.14%) had normal occlusion, (6o)05%) had CL.l malocclusion had CL.II malocelusion and (0.45%) who had CLIII malocclusion. The )%3,77( differences in prevalence of maloeclusion was statistically significant between these groups. On the other hand. This statistical difference was significant in eases with extraction than those cases without extraction (P< 0.05). clearly, there is a need for further epidemiologeal research aiming to increase the knowledge a bout the prevalence and type of malocclusion as well as the extent of need & demand for orthodontic treatment.